2002
DOI: 10.1007/s00259-002-0889-z
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial distribution of 18F-FDG and 99mTc-sestamibi on dual-isotope simultaneous acquisition SPET compared with PET

Abstract: A dual-isotope simultaneous acquisition (DISA) single-photon emission tomography (SPET) protocol with fluorine-18 fluorodeoxyglucose ((18)F-FDG) and a technetium-99m labelled flow tracer is attractive because it permits assessment of both myocardial glucose utilisation and flow within a single study. Differences in physical and physiological characteristics between (18)F-FDG and the (99m)Tc-labelled flow tracer, however, may cause differences in myocardial activity distribution between the agents. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Direct comparison of the perfusion tracers 99m Tc-sestamibi/FDG DISA SPECT and 13 N-ammonia PET are scarce. Only Matsunari et al published a small study about the concordance and discordance of 99m Tc-sestamibi/ FDG DISA SPECT and 13 N-ammonia/FDG PET in 10 patients with CAD, by using the difference between the perfusion tracer and 18 FDG of both techniques [133]. They found a good overall concordance between the activity distribution of FDG and flow tracers of both techniques.…”
Section: Fdg Spect and Disa Spectmentioning
confidence: 95%
See 1 more Smart Citation
“…Direct comparison of the perfusion tracers 99m Tc-sestamibi/FDG DISA SPECT and 13 N-ammonia PET are scarce. Only Matsunari et al published a small study about the concordance and discordance of 99m Tc-sestamibi/ FDG DISA SPECT and 13 N-ammonia/FDG PET in 10 patients with CAD, by using the difference between the perfusion tracer and 18 FDG of both techniques [133]. They found a good overall concordance between the activity distribution of FDG and flow tracers of both techniques.…”
Section: Fdg Spect and Disa Spectmentioning
confidence: 95%
“…As with PET studies, metabolic activity measured by FDG SPECT is generally interpreted in combination with a flow tracer. For this purpose, a dualisotope simultaneous acquisition (DISA) SPECT protocol with FDG and 99m Tc-perfusion tracer is attractive because it enables assessment of myocardial glucose utilization and perfusion in a single study ( Figure 4) [128,129,133]. DISA SPECT shortens the duration of procedure, with the advantage of an identical geometric registration of Figure 4.…”
Section: Fdg Spect and Disa Spectmentioning
confidence: 99%
“…FDG is a tracer for PET imaging, but can also be used in conjunction with conventional gamma cameras using ultra-high energy collimators [11]. A recent study showed an overall good agreement between 99m Tc-sestamibi/FDG DISA SPECT and PET for the assessment of myocardial viability in patients with severe left ventricular dysfunction [12].…”
Section: Viability Assessment: Pet or (Disa) Spect?mentioning
confidence: 98%
“…Additionally, cardiac dual-isotope SPECT imaging involving a PET radionuclide has been described in several papers (8)(9)(10)(11)(12). Two of these studies (8,12) included a comparison of 99m Tc-tracer imaging with and without the presence of 511 keV by scanning the same subjects for 99m Tc-sestamibi/tetrofosmin twice, before and after 18 F-FDG injection.…”
Section: Earlier Workmentioning
confidence: 99%